Reward and Punishment Policy in Improving Student Honesty and Discipline - Melynda Khoirun Nisa’; Muhammad Munif (Al-Qalam Institue, 2024)
Teachers in schools today face various challenges in shaping students' personalities due to environmental influences, technological advances, and easily accessible media. One approach used to improve students' character is character education. This study aims to analyze the formation of student discipline through punishment and rewards. Data collection techniques include observation, documentation, and interviews with teachers at Insan Terpadu Middle School, while data analysis techniques use triangulation. The study results show that teachers know the importance of character education and apply it in learning. Teachers give awards to students who excel and educational punishments to students who break the rules, not in the form of physical violence. Students respond positively to the implementation of rewards and punishments, which are well received. The impact of implementing this system on student discipline and honesty is significant. Namely, students becoming more disciplined and responsible. In conclusion, implementing appropriate rewards and punishments can improve student discipline and honesty if done correctly and consistently.